A question prompt sheet for adult patients with chronic kidney disease. Issue 1 (December 2016) - Lederer, Swati; Fischer, Michael; Gordon, Howard; Wadhwa, Anuradha; Popli, Subhash; Gordon, Elisa
Abstract Background Patients with chronic kidney disease (CKD) commonly have unmet information needs. Greater patient participation in healthcare discussions can address these needs and improve health outcomes. We developed a patient-centered question prompt sheet (QPS) to engage CKD patients in healthcare conversations. Methods We conducted a two phase, mixed-methods, cross-sectional study involving semi-structured telephone interviews. Patients with an estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m2, on dialysis, or with a kidney transplant were recruited from one Veterans Affairs (VA) nephrology clinic. Phase 1 interviews included open-ended questions assessing patients' CKD-related information needs and generated a preliminary 67-item QPS. Phase 2 interview participants rated the importance of asking each question on a 5-point Likert scale and provided open-ended feedback. All participants rated their willingness to use a CKD-QPS. Input from patient ratings, a multidisciplinary team, and from members of the National Kidney Disease Education Program (NKDEP) Coordinating Panel helped to shorten and refine the QPS. A qualitative thematic approach was used to analyze open-ended responses. Quantitative data were analyzed for means and proportions. Results Eighty-five patients participated. Most were male (97 %), non-Hispanic white (71 %), and mean age was 67 years. Patients desired more information about CKD, particularly dialysis/transplant, and the relationship between CKD and comorbid medical conditions. The final QPS included 31-questions divided into 7 CKD subtopics. Most patients (88 %) reported being 'completely' or 'very' willing to use a CKD-QPS in future doctor visits. Conclusions CKD patients have unmet information needs. We developed a QPS to engage CKD patients in healthcare discussions and to facilitate patient-centered care. Future research should assess whether the CKD-QPS addresses patients' information needs, enhances doctor-patient communication, and improves health outcomes.